Flow Characteristics and Loss Mechanism of Tip Leakage Flow in Mining Contra-Rotating Axial Flow Fan - Yongping Chen; Ronghua Liu; Wenqing Peng; Shiqiang Chen (Applied Sciences)
Tip leakage flow interacts with the mainstream, impacting the energy transmission process within the impeller of the fan and causing a significant flow loss. Understanding the flow characteristics within the impeller is a prerequisite and foundation for achieving efficient operation of the fan. Therefore, numerical simulations and experimental methods were employed to obtain the internal flow field of the mining counter-rotating axial flow fan, and the influence of flow rate on the tip leakage flow pattern was mastered. The spatial trajectory of the leakage vortex was quantified, and the distribution characteristics of the backflow were explored. The mechanism of energy loss caused by the leakage flow was revealed. The research findings indicate that when the flow rate exceeds 1.0 QBEP (QBEP is flow rate at the best efficiency point), the complex flow field near the blade tip is mainly caused by the tip leakage flow. However, the tip leakage flow and the leading edge overflow are the main factors causing disturbances in the flow field within the impeller at small flow rates. At large flow rates, the starting positions of the tip leakage vortex cores for both the front and rear impellers are located near the middle of the blade tip. As the flow rate decreases, the starting position of the vortex core gradually shifts toward the leading edge point, and the vortex structure evolves from an initial circular shape to an elliptical shape. The tip leakage flow and the leading edge overflow are the main cause of the backflow at the impeller inlet. The helical vortices caused by the tip leakage flow and the leading edge overflow, as well as the backflow in the impeller, are the key factors causing energy loss in the tip clearance flow field.